Long-term urinary dysfunction after rectal cancer surgery - Del Río, C.; Sánchez-Santos, R.; Oreja, V.; De Oca, J.; Biondo, S.; Parés, D.; Osorio, A.; Martí-Ragué, J.; Jaurrieta, E. (Colorectal disease, 2004)
Objective  Urinary dysfunction is a well‐known complication of rectal surgery, secondary to injury to the autonomic nervous plexus. The object of this study was to evaluate the incidence, prevalence and type of micturition disorders following rectal cancer surgery and their reversibility during long‐term follow‐up. Patients and methods  A prospective study of 45 patients who underwent surgery for rectal cancer between 1993 and 1998 was undertaken. Those with pre‐operative urinary dysfunction were excluded after sequential uroflowmetry and clinical interview. Ten of the surgical interventions were high anterior resections, 18 low anterior resections, and 17 abdominoperineal amputations. Pre‐operative radiotherapy was performed in 47.9% of patients. All patients underwent sequential uroflowmetry and a clinical interview 3 and 12 months after the intervention. Subjects who presented micturition disorders underwent urodynamic examination The follow up period was three years. Results  Three months after surgery alterations were found in 14 (31.3%) patients; the most frequent were stress incontinence, urinary tenesmus and the urge to urinate. At the 12‐month assessment only 6 (13.3%) patients had urinary symptomatology or uroflowmetry abnormalities. After three years, micturition disorders persisted in 3 (6.6%) patients. Conclusion  Urinary dysfunction after rectal cancer excision is associated with a high degree of reversibility. Seventy‐eight percent of the alterations detected after three months and 50% of those that persisted after a year disappeared during follow up.